Inventory of the historical Dianthus sylvestris herbarium materials from Herbarium Croaticum and Herbarium Ivo and Marija Horvat - Terlević, Ana (Array, 2020)
In order to initiate a taxonomical revision of the Dianthus sylvestris group, an inventory of historical herbarium materials from ZA and ZAHO collections was conducted. Herbarium specimens of D. sylvestris group from these two herbaria were digitized and the data from the original herbarium labels were inserted in the Flora Croatica Database. A total of 344 herbarium sheets were digitized and six taxa (D. sylvestris Wulfen in Jacq. ssp. sylvestris, D. sylvestris ssp. tergestinus (Rchb.) Hayek, D. sylvestris ssp. longicaulis (Ten.) Greuter et Burdet, D. sylvestris ssp. nodosus (Tausch) Hayek, D. siculus C. Presl and D. arrosti C. Presl) were registered within studied collections. Inventory of herbarium sheets from ZA and ZAHO historical collections provided a significant insight into historical distributional data of D. sylvestris taxa related to the area of the Balkan Peninsula, which is a prerequisite for accurate taxonomic/ geographic sampling for further morphological and molecular analyses.